2014
DOI: 10.1177/1040638714536560
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two methods for measurement of equine insulin

Abstract: Diagnosis of equine hyperinsulinemia requires an accurate method for quantification of equine insulin concentrations. The objectives of the current study were to compare 2 commercially available techniques for measurement of equine insulin, the radioimmunoassay (RIA) and chemiluminescent immunoassay (CIA). Recovery was poor for both assays, but worse for the CIA. Serial dilution of a high endogenous insulin sample yielded better linearity for the RIA ( r2 = 0.99, P < 0.001) than the CIA ( r2 = 0.92, P = 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 12 publications
(23 reference statements)
2
20
0
Order By: Relevance
“…This study used the radioimmunoassay (RIA) to measure insulin concentrations, whereas in the UK a chemiluminescence immunoassay (CL) is widely used by commercial laboratories. Previous studies have reported that the two techniques are inequivalent [23]. When two RIAs were compared with the CL, all differed significantly with values from the CL being significantly lower than those from the two RIAs [20].…”
Section: Discussionmentioning
confidence: 75%
“…This study used the radioimmunoassay (RIA) to measure insulin concentrations, whereas in the UK a chemiluminescence immunoassay (CL) is widely used by commercial laboratories. Previous studies have reported that the two techniques are inequivalent [23]. When two RIAs were compared with the CL, all differed significantly with values from the CL being significantly lower than those from the two RIAs [20].…”
Section: Discussionmentioning
confidence: 75%
“…Due to a lack of LC-MS in our study, potential over- or underestimation of the assays examined could not be evaluated. Banse and colleagues [7] compared the human-specific RIA 8 with another commercially available CLIA9 which is often used for the measurement of equine insulin in both clinical practice and research. Both the human-specific RIA 8 and the CLIA 9 resulted in poor recovery rates within each assay and showed poor accordance.…”
Section: Discussionmentioning
confidence: 99%
“…Several immunoassay methods for the quantification of insulin in equine serum or plasma samples are commercially available. However, due to the use of different methods for quantifying equine insulin, discrepancies between results obtained from different studies have occurred [6, 7]. Since no assay with a specific antibody against equine insulin is available, most of the commercial immunoassays are based on antibodies directed against human or non-equine insulin.…”
Section: Introductionmentioning
confidence: 99%
“…Confounding the problems associated with the use of basal serum insulin concentration is the variety of laboratory assays currently used to determine equine insulin concentration [61][62][63][64][65]. All of the currently available tests suffer limitations and this is an area in desperate need of further research.…”
Section: Basal Serum Insulin Concentrationmentioning
confidence: 99%